ANALISIS KEPUASAN KONSUMEN PERUSAHAAN OTOBUS (PO) WASPADA BENGKULU - Markoni Markoni (Pascasarjana Universitas Halu Oleo, 2020)
This study aims to determine the level of customer satisfaction PO Waspada Bengkulu. The sample size is 75 people, and the incidental sampling technique. Data collection using a questionnaire, and then analyzed using the Customer Satisfaction Index (CSI) method, taking into account the level of consumer interest and employee performance levels. There are ten service elements studied, which include Employee Friendliness, Service Speed, Clarity of Departure Information, Waiting Room Comfort, Environmental Security, Passenger and Goods Safety, Ease of Access, Clarity of Rights and Obligations of Passengers, Clarity of Service Procedures, and Justice in Service Delivery. Customer Satisfaction Index (CSI) PO. Waspada Bengkulu that was obtained amounted to 74.1979 including Category (B) or Good. This shows that consumers of PO.Waspada Bengkulu can be said to be satisfied with the service they receive from the Company's employees. Judging from each service in general. Consumer PO. Waspada Be ngkulu satisfied with the service they received, because of the ten Service Elements studied, only one was included in Category (C) or not good, namely the service element, while the others were included in Category (B) or Good, there was even one element. namely Excessive Access Speed due to Very Good Employee Performance (A) while the interests of Consumers are ordinary. To maintain the quality of service to consumers and consumers who are satisfied with the services provided, it is suggested to the PO Management. Waspada Bengkulu to establish Service Quality Standards and establish Guidelines for Implementation of Service Quality Standards or Standard Operating Procedures (SOPs), supervise and evaluate periodically the implementation of services to consumers.